THE EFFECT OF AREA AND SITE OF TYMPANIC MEMBRANE PERFORATIONS ON HEARING THRESHOLD AMONG SUDANESE PATIENTS - Ahmed Elhaj, Abu sufian Hassan; Abdalla, Mohammad Bushara; Abubakar AbdallaM, Haydar (Gezira Journal of Health Sciences; Vol 4 No 1 (2008), 2005)
Background : Chronic otitis media is one of the commonest otological problems among Sudanese children and adults. The disease presents with perforations of the eardrum, discharging ears and varying degrees of hearing loss. Objective: The objective of this work is to study the effect of the area and the site of the tympanic membrane perforation on hearing threshold among Sudanese patients. Patients & Methods : This is a prospective hospital-based study conducted at Ibn Sina and Khartoum Teaching Hospitals-Otolaryngology Departments (E.N.T), in the period from 1 April – to the 30 of July 2002. Information from both the control and study subjects was taken, using protested questionnaire. Twenty-five normal subjects (50 ears) were taken as a control group selected randomly from the healthy population; their hearing thresholds were tested in order to find a reference level. Seventy-one consequtive patients with uni - or bilateral chronic suppurative otitis media (100 perforated ears) were taken as a study group. Results : The hearing threshold of the control Sudanese subjects was 17 dB. This was obtained by computing the mean for the human speech frequencies (500, 1000, 2000Hz). The lower frequencies were affected regardless of side, site and area of the perforation. Conductive hearing loss was the commonest type ( 79% ). The commonest site of the perforations was the central site ( 90% ) followed by posteroinferior 3%. The commonest area of tympanic membrane perforations was the subtotal area ( 54% ), followed by large central perforations (25%). The greatest hearing loss was found to be in the posteroinferior and anterio-superior perforation of the drum compartment. Conclusion and recommendations From this study, we can conclude that regardless of the area, the site of tympanic membrane perforation is the most important factor affecting hearing threshold. The posterior central perforation having the greater effect for this reason, any patients with the posteroinferior and anterio-superior perforations should have repair of tympanic membrane (myringoplaty).